Introduction: Corpus linguistics and the Nordic languages. Issue 2 (16th October 2014) - Andersen, Gisle; Hardt, Daniel; Andersen, Gisle; Hardt, Daniel
<x content-type="archive" xml:space="preserve">Abstract</x> Recent decades of research in linguistics have seen a shift towards empirical methods and an increased use of data from corpora as a basis for making claims about language (Sampson 2005). This trend has made its mark on research on the Nordic languages also, and the current special issue aims to show some of the breadth of research in this field. The issue is in its entirety devoted to contributions that use the methodology of corpus linguistics on Nordic language data. This includes research that investigates both historical and contemporary aspects of the languages of the Nordic region.